التصورات الإجتماعية لدى الطلبة المقيمين حول ظاهرة العنف بالأحياء الجامعية: دراسة ميدانية بالإقامات الجامعية لولاية الوادي - جلول, أحمد (University of Oum Elbouaki جامعة أم البواقي, 2017)
اهتمت هذه الدراسة بأحد المشكلات التي تعاني منها مؤسسات التعليم العالي عموما والأحياء الجامعية على وجه الخصوص ألا و هي ظاهرة العنف، حيث تأتي الدراسة الحالية لتتعرض التصورات الاجتماعية لدى الطلبة المقيمين حول ظاهرة العنف بالأحياء الجامعية والتي تندرج ث ضمن البحوث الوصفية وخاصة منها المتعلقة بمشكلات المؤسسات الجامعية، بحيث تمحورت إشكالية الدراسة حول الكشف على التصورات الاجتماعية لدى الطلبة المقيمين حول ظاهرة العنف بالأحياء الجامعية وللإجابة الإشكالية على هذه اعتمدنا على خمس فرضيات والتي كانت أبعاد حول خمس (الإيواء، خدمات الإطعام ، المرافق الترفيهية والعلمية ،المنظمات الطلابية، الطالب) و التي يمكن أن يفسر بها الطلبة المقيمين ظاهرة العنف بالأحياء الجامعية حسب تصوراتهم الاجتماعية. و قد اعتمدنا في هذه الدراسة على الاستمارة كأداة لجمع البيانات، و التي أجريت بالأحياء الجامعية المتواجدة بولاية الوادي على عينة عددها 350 طالب من مجموع كلي بلغ 3095 طالب. و بعد عرض النتائج و معالجتها ومن ثم مناقشتها تمكنا من إثبات صحة جميع الفرضيات الخمس للدراسة و قد استطعنا من خلال هذه الدراسة الوصول إلى مجموعة من النتائج نذكر منها: - هناك تصورا اجتماعيا لدى الطلبة المقيمين بوجود عوامل تتعلق بالإيواء في تفسيرهم لظاهرة العنف بالأحياء. - هناك تصورا اجتماعيا لدى الطلبة المقيمين بوجود عوامل تتعلق بخدمات الإطعام في تفسيرهم لظاهرة العنف بالأحياء الجامعية. - هناك تصورا اجتماعيا لدى الطلبة المقيمين بوجود عوامل تتعلق بالمرافق الترفيهية و العلمية في تفسيرهم لظاهرة العنف بالأحياء الجامعية. - هناك تصورا اجتماعيا لدى الطلبة المقيمين بوجود عوامل تتعلق بالمنظمات الطلابية في تفسيرهم لظاهرة العنف بالأحياء الجامعية. - هناك تصورا اجتماعيا لدى الطلبة المقيمين بوجود عوامل تتعلق بالطالب الجامعي في تفسيرهم لظاهرة العنف بالأحياء الجامعية. و في الأخير اختتمت الدراسة بمجموعة من الاقتراحات بناءا على النتائج المتوصل إليها و التي نراها تخدم هذا الموضوع. This study focused on one of the problems faced by institutions of higher education in general and in particular the university accommodationsnamely the phenomenon of violence, accordingly the current study exposed to the topic of social perceptions among resident students about the phenomenon of violence in the university accommodations, which belongs the descriptive research, especially those related to the problems of university institutions. So, the problem of the study centered on the detection of social perceptions among resident students about the phenomenon of violence in the university accommodations. To answer this problem, we relied on five hypotheses which were about five dimensions(residence, catering services, recreational and scientific facilities, student organizations, and student) by whichresident students can interpretthe phenomenon of violence in university accommodations according to their social perceptions. We used a questionnaire in the current studyas a tool for collecting, which was conducted in the university accommodations existing in El Ouedon a sample consisted of 350 students out of a total of 3095 students. After the results presentation, data processing and discussion, we were able to prove the validity of all the five hypotheses. So, the findings were as follows: - There is a social perception among resident students about the existence of factors related to residence in their interpretation of the phenomenon of violence in university accommodations. - There is a social perception among resident students about the existence of factors related to catering services in their interpretation of the phenomenon of violence in university accommodations. - There is a social perception among resident students about the existence of factors related to recreational and scientific facilities in their interpretation of the phenomenon of violence in university accommodations. - There is a social perception among resident students about the existence of factors related to student organizations in their interpretation of the phenomenon of violence in university accommodations. - There is a social perception among resident students about the existence of factors related to the university student in their interpretation of the phenomenon of violence in university accommodations. At last, the study concluded by a set of proposals based on the obtained results serving this subject.
أطروحة دكتوراه في علم النفس تخصص علم النفس الاجتماعي
Keywords: العنف، التصورات الإجتماعية، التصور، العدوان، الانحراف، الأحياء الجامعية.; Violence, social perceptions, perception, aggression, delinquency, university neighborhoods.